Development of a Website as an Instructional Tool for Computer Science Subject to Support Student Self-Learning: Student Needs Analysis - Bt Mohamad, Saadiah; Bt Hashim, Nur Dini; Zahirah Bt Abdul Rahman, Nur Syafiqah (Department of Informatics, Universitas Syiah Kuala, 2024)
This research aims to enhance the Teaching Aids content through a website developed based on a study involving Computer Science educators. An analysis of student requirements is essential to ensure that the website's content effectively supports students in visualizing the entire curriculum framework and fostering self-directed learning in programming. Using the ADDIE design model, the study aims to assess students' comprehension of curriculum structures and their proficiency in programming topics according to the Project Work Assessment Task Manual (MTPKP).A questionnaire was distributed to 166 students enrolled in Computer Science courses across 11 secondary schools in the Kubang Pasu district in 2023 to gather data. Quantitative analysis revealed moderate levels of understanding among students regarding the curriculum structure (mean score 3.62) and programming topic mastery (mean score 3.66) based on MTPKP criteria.The study identified three new elementsAssessment, Time and Test Schedule, and Path to Excellence after SPMto potentially integrate into the website. These additions are aimed at aiding students in comprehending the Computer Science curriculum structure and formulating personalized learning strategies. Additionally, the research offers insights for educators to develop programming exercises that better cater to students' needs, thereby enhancing their programming skills effectively.